Seroadaptive Practices: Association with HIV Acquisition among HIV-Negative Men Who Have Sex with Men - Vallabhaneni, Snigdha; Li, Xin; Vittinghoff, Eric; Donnell, Deborah; Pilcher, Christopher D.; Buchbinder, Susan P. (PLOS ONE, 2012)
Background Although efficacy is unknown, many men who have sex with men (MSM) attempt to reduce HIV risk by adapting condom use, partner selection, or sexual position to the partner’s HIV serostatus. We assessed the association of seroadaptive practices with HIV acquisition. Methodology/Principal Findings We pooled data on North American MSM from four longitudinal HIV-prevention studies. Sexual behaviors reported during each six-month interval were assigned sequentially to one of six mutually exclusive risk categories: (1) no unprotected anal intercourse (UAI), (2) having a single negative partner, (3) being an exclusive top (only insertive anal sex), (4) serosorting (multiple partners, all HIV negative), (5) seropositioning (only insertive anal sex with potentially discordant partners), and (6) UAI with no seroadaptive practices. HIV antibody testing was conducted at the end of each interval. We used Cox models to evaluate the independent association of each category with HIV acquisition, controlling for number of partners, age, race, drug use, and intervention assignment. 12,277 participants contributed to 60,162 six-month intervals with 663 HIV seroconversions. No UAI was reported in 47.4% of intervals, UAI with some seroadaptive practices in 31.8%, and UAI with no seroadaptive practices in 20.4%. All seroadaptive practices were associated with a lower risk, compared to UAI with no seroadaptive practices. However, compared to no UAI, serosorting carried twice the risk (HR = 2.03, 95%CI:1.51–2.73), whereas seropositioning was similar in risk (HR = 0.85, 95%CI:0.50–1.44), and UAI with a single negative partner and as an exclusive top were both associated with a lower risk (HR = 0.56, 95%CI:0.32–0.96 and HR = 0.55, 95%CI:0.36–0.84, respectively). Conclusions/Significance Seroadaptive practices appear protective when compared with UAI with no seroadaptive practices, but serosorting appears to be twice as risky as no UAI. Condom use and limiting number of partners should be advocated as first-line prevention strategies, but seroadaptive practices may be considered harm-reduction for men at greatest risk.